Timing Is of the Essence: Improvement in Perception During Active Sensing - Concha-Miranda, Miguel; Ríos, Javier; Bou, Joaquín; Valdes, Jose Luis; Maldonado, Pedro E. (Frontiers in Behavioral Neuroscience, 2019)
Active sensing refers to the concept of animals perceiving their environment while involving self-initiated motor acts. As a consequence of these motor acts, this activity produces direct and timely changes in the sensory surface. Is the brain able to take advantage of the precise time-locking that occurs during active sensing? Is the intrinsic predictability present during active sensing, impacting the sensory processes? We conjecture that if stimuli presentation is evoked by a self-initiated motor act, sensory discrimination and timing accuracy would improve. We studied this phenomenon when rats had to locate the position of a brief light stimulus, either when it was elicited by a warning light (passive condition) or when it was generated by a lever press (active condition). We found that during the passive condition, rats had 66% of correct responses, vs a significantly higher 77% of correct responses in active condition. Furthermore, reaction times reduced from 1181 ms during active condition to 816 ms during passive condition For the latter condition, the probability of detecting the side of the light stimulus was negatively correlated with the time lag between the motor act and the evoked light and with a 38% reduction on performance per second of delay. These experiment shows that the mechanism that underlies sensory improvement during active behaviors have a constrained time dynamic, where the peak performances occur during the motor act, decreasing proportionally to the lag between the motor act and the stimulus presentation. This result is consistent with the evidence already found in humans, of a precise time dynamic of the improvement of sensory acuity after a motor act and reveals an equivalent process in rodents. Our results support the idea that perception and action are precisely coordinated in the brain.